Anthropology of Color Interdisciplinary Multilevel Modeling - MacLaury, Robert; Paramei, Galina; Dedrick, Don (John Benjamins Publishing Company, 2007)
The field of color categorization has always been intrinsically multi- and inter-disciplinary, since its beginnings in the nineteenth century. The main contribution of this book is to foster a new level of integration among different approaches to the anthropological study of color. The editors have put great effort into bringing together research from anthropology, linguistics, psychology, semiotics, and a variety of other fields, by promoting the exploration of the different but interacting and complementary ways in which these various perspectives model the domain of color experience. By so doing, they significantly promote the emergence of a coherent field of the anthropology of color.